Majlis apresiasi pelajar: Faculty of Business and Management 2023 - UiTM, Faculty of Business Management (UiTM, 2024)
In this issue, you will discover a vibrant array of stories that showcase not only our academic milestones but also the innovative projects and community contributions spearheaded by our faculty and students. From poneering research to meaningful community outreach, FBM is continually setting itself apart as acentre of academic distiction and visionary leadership.